The Army Officers' Professional Ethic: Past, Present, and Future - Scholar's Choice Edition - Moten, Matthew 1960- (Professional military ethics monograph series, 2010)
"This monograph surveys the history of the Army's professional ethic, focusing primarily on the Army officer corps. It assesses today's strategic, professional, and ethical environment. Then it argues that a clear statement of the Army officers' professional ethic is especially necessary in a time when the Army is stretched and stressed as an institution. The Army officer corps has both a need and an opportunity to better define itself as a profession, forthrightly to articulate its professional ethic, and clearly to codify what it means to be a military professional."--Summary